Biološke učinkovine pri zdravljenju Crohnove bolezni in ulceroznega kolitisa - Bratkovič, Tomaž (Farmacevtski vestnik, 2008)
Crohn's disease and ulcerative colitis (conditions together known as inflammatory bowel disease) are chronic inflammatory diseases affecting the bowel, whose causes remain unknown. In the last decades, however, our understanding of the pathophysiology of these conditions has enormously advanced. Conventional treatment of inflammatory bowel disease largely relies on the use of anti-inflammatory or immunosuppressive drugs that tend to act rather nonspecifically, often causing severe adverse effects that can even result in discontinuation of treatment. It is thus clear that development of safer and more effective drugs selectively blocking the inflammatory cascade is needed. In the European Union and the United States two and three biologic agents, respectively have already been approved for the management of Crohnćs disease and ulcerative colitis unresponsive to conventional treatment and development of several more is on the way. This review reports on current status of biological therapy for inflammatory bowel disease.
Keywords: biološka zdravila; Crohnova bolezen; črevesne bolezni; therapy; ulcerozni kolitis; zdravljenje